National elections and tail risk: International evidence - Li, Qingyuan; Li, Si; Xu, Li (Journal of Banking & Finance, 2018)
We investigate stock tail risk around national elections worldwide over the period of 1982–2012. We find that firm stock is less likely to crash during the election years, and is more likely to crash during the post-election period. This inter-temporal pattern is consistent with the suppression of negative information when there is heightened political uncertainty around elections and with the subsequent release of adverse news when the uncertainty is reduced. Further analysis shows that the impact of political uncertainty on tail risk is stronger in countries with poorer investor protection, fewer electoral checks and balances, more uncertain election outcomes and pro-business incumbent governments, in industries which are more politically sensitive, and in firms with larger information asymmetry.